The impact of nonperforming loans on cross-border bank lending implications for emerging market economies - Park, Cyn-Young; Shin, Kwanho ([Manila] Asian Development Bank, 2020)
This brief suggests how policy makers can tackle the likely rise in nonperforming loans (NPLs) as a result of the coronavirus disease (COVID-19) pandemic to prevent a debt crisis.
Keywords: Bank loans; Banks and banking; Bank loans -- Management,COVID-19 (Disease).; Electronic books